COVID-19 and the Health Industry: A Test of Market Efficiency - Bacon, Frank W.; Howell, William N. (Journal of Applied Business and Economics, 2021)
The World Health Organization declared the COVID-19 coronavirus outbreak as a global pandemic on March 11, 2020. How does the market react to a global pandemic announcement? How efficient is the market? The purpose of this study is to test for semi-strong form market efficiency. Will the healthcare industry show excess gains? A link between the market and pandemics can be inferred but has not been heavily studied. In the efficient market hypothesis, Fama (1970) proposes that in semi-strong form market efficiency, all public information is factored into the market and no investor can achieve a risk-adjusted, above normal return. To study this relationship, S&P 500 data on 10 healthcare firms was collected for several days surrounding the announcement and standard event study methodology from finance literature was used. Evidence here supports the expected positive signal associated with the sample firms and pandemic announcement. Likewise, the results support the semi-strong form efficient market hypothesis and suggests the possibility of trading on this information up to 24 days before the announcement.